Dampak Bencana Alam terhadap Kesehatan Reproduksi dan Perinatal - Baiq Zulvita Rahayu; Fitria Yulastini (Pusat Riset dan Inovasi Nasional, 2026)
Background: The increasing frequency of natural disasters poses substantial threats to women’s reproductive and perinatal health. These events disrupt essential health services, intensify psychosocial stress, and create hazardous living environments that disproportionately affect pregnant women. Methods: A Narrative Literature Review was conducted to synthesize evidence from recent cohort studies, systematic reviews, mixed-methods designs, and qualitative research exploring disaster-related reproductive and perinatal outcomes. Results: Findings demonstrate consistent associations between disaster exposure and adverse outcomes, including preterm birth, low birth weight, menstrual disturbances, genital infections, and elevated prenatal stress. Damage to health infrastructure, limited antenatal care access, population displacement, and inadequate sanitation further exacerbate maternal vulnerability. Risks are greatest in low-resource settings and during first-trimester exposure. Conclusion: Natural disasters produce multidimensional risks for reproductive and perinatal health. Implementation of proper Disaster Management, integrating mental-health support, and adopting gender-responsive policies is crucial for mitigating maternal and neonatal harm.